Emergent by Design: Performance and Transformation at Infosys Technologies - Garud, Raghu; Kumaraswamy, Arun; Sambamurthy, V. (Organization Science, 2006)
We explore how organizations may be designed to transform themselves even as they continue to perform seamlessly on a day-to-day basis. Our inquiry frame recognizes that organizational designs comprise several elements—people, technologies, processes, and governance. Our study of an exemplary organization, Infosys Technologies, yields two insights. At Infosys, each design element is seeded with generative properties. As these design elements interact, reinforcing and balancing one another, an overall organizational platform of resources, capabilities, and options emerges. The company draws on this emergent platform to perform in real time even as it transforms itself to adapt to changing environments.